2014
DOI: 10.1097/hp.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Increased Occupational Radiation Doses

Abstract: The increased occupational doses resulting from the Chernobyl nuclear reactor accident that occurred in Ukraine in April 1986, the reactor accident of Fukushima that took place in Japan in March 2011, and the early operations of the Mayak Production Association in Russia in the 1940s and 1950s are presented and discussed. For comparison purposes, the occupational doses due to the other two major reactor accidents (Windscale in the United Kingdom in 1957 and Three Mile Island in the United States in 1979) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…The mean cumulative internal liver dose, largely from alpha-particle exposure, is 0.31 Gy, with a maximum of 36 Gy [ 35 ]. This compares with average annual effective doses of up to 1000 mGy recorded in the late 1940s, as reported by [ 38 ]. During 1948–1953, when doses to Mayak workers were the highest, the unshielded dosimeters had significant variability in photon energy dependence and angular response, and bias by high-energy beta exposures provided overestimates of doses for workers in some settings.…”
Section: Dose Rates and Corresponding Cumulative Doses Of Human Cohorsupporting
confidence: 84%
See 2 more Smart Citations
“…The mean cumulative internal liver dose, largely from alpha-particle exposure, is 0.31 Gy, with a maximum of 36 Gy [ 35 ]. This compares with average annual effective doses of up to 1000 mGy recorded in the late 1940s, as reported by [ 38 ]. During 1948–1953, when doses to Mayak workers were the highest, the unshielded dosimeters had significant variability in photon energy dependence and angular response, and bias by high-energy beta exposures provided overestimates of doses for workers in some settings.…”
Section: Dose Rates and Corresponding Cumulative Doses Of Human Cohorsupporting
confidence: 84%
“…During 1948–1953, when doses to Mayak workers were the highest, the unshielded dosimeters had significant variability in photon energy dependence and angular response, and bias by high-energy beta exposures provided overestimates of doses for workers in some settings. Efforts were made to correct for those estimation biases, but such corrections likely had substantial uncertainties [ 33 , 38 ]. In addition, before 1957 unmeasured intermediate and fast neutrons were thought to have contributed 10–15% of the total dose [ 36 ].…”
Section: Dose Rates and Corresponding Cumulative Doses Of Human Cohormentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and validity of the official doses depend on the time period considered and the type of work performed (Ilyin 1995; Chumak 2007; Bouville and Kryuchkov 2014). Reviews of official doses have revealed their possible bias and low accuracy, to degrees strongly correlated with the affiliation of the cleanup worker and, therefore, the type of dosimetric monitoring received at the time of cleanup (Chumak 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Uranium processing workers also come in contact with other types of radiation (e.g., gamma-ray, long-lived radionuclides from uranium ore dust) and non-radioactive (e.g., fine or silica dust) exposures from the ore dust, but less to RDP exposures, typical for uranium underground miners. Average annual effective radiation doses in this group have been reported at 10 millisievert (mSv) compared to <5 mSv for other workers of the fuel cycle (Bouville and Kryuchkov 2014 ). Several studies reported substantially higher cumulative lifetime occupational gamma-ray exposures for uranium processing workers (Kreuzer et al 2015 ; Zablotska et al 2013 ) compared to external radiation exposures of nuclear reactor workers (Cardis et al 2007 ; Muirhead et al 2009 ).…”
Section: Introductionmentioning
confidence: 64%